Advokasi Kesetaraan Gender melalui Pendidikan Sosial: Studi Peran Duta Genre - Arinal Haq Fauziah; Ishlakhatus Sa’idah (IAIN Madura, 2025)
This study aims to explore the role of Duta Genre as an agent of change in raising public awareness of gender equality through a social education approach in Sampang Regency. Social education, which emphasizes social interaction and community empowerment, is a key strategy in overcoming cultural and structural barriers that limit women's access to equal education and social services. This study uses a qualitative method with a case study approach, involving in-depth interviews and observations of the implementation of the Duta Genre program. The results of the study indicate that this program effectively raises awareness among adolescents and the community about the importance of gender equality through various activities, such as peer counseling, discussion groups, and social campaigns. However, challenges in the form of cultural resistance and limited policy support are still obstacles in the implementation of this program. The findings of this study emphasize the importance of cross-sector collaboration to strengthen the impact of the program, while encouraging the creation of a more inclusive and gender-equitable environment.